Factors Affecting Customer to Use E-Wallet With Brand Image As Moderating Variable An Evidence of E-Wallet Brand LinkAja Users - Mudi Irawan (Journal of Sustainable Community Development (JSCD), 2023)
Non-cash transaction become popular in Indonesia during Covid 19 because of health and safety reason. According to internal report, LinkAja is succeeded to maintain the good level of awareness (83%) from year on year. However, LinkAja`s brand performance is experiencing a significant drop in consideration (35%) and actual usage (24%). Thus, the aim of this study is to investigate factors affecting LinkAja customer to use e-Wallet with Brand Image as moderating variables. Within Quantitative Method and survey, the author collected sample from 113 LinkAja e-Wallet Customers in Jabodetabek during March 2022. The study found that Perceived Usefulness and Perceived Ease of Use have a significant effect on Intention to Use, and Intention to Use e-Wallet has a significant effect on Actual Usage of e-Wallet. In the contrast, Brand Image has no moderating effect between Intention to Use e-Wallet on Actual Usage of e-Wallet. This study provides several theoretical and practical guidelines for Finance Technology and Brand Management in Indonesia and other country. Author recommended LinkAja must focus their strength on product services and experience and marketing effort on branding. There are limitation of the study, which are cross-sectional time horizon, the sample was limited to 113 respondents, and the result was limited to Jakarta Area only. Authors recommended a future study to continue investigating e-Wallet phenomenon in other area with a broader time.